(untitled) (Transactions of the Association of European Schools of Planning, 2019)
In summer 2017 during the Annual AESOP Congress in Lisbon we were delighted and proud to present the inaugural issue of Transactions of the Association of the European School. Starting this journal took the editorial team on an enjoyable (ad)venture where we discussed format innovations, approaches, and procedures that would be suited to encapsulating the very inclusive, open-minded and nurturing character of the AESOP community while also measuring up to academic standards and scrutiny. It was a venture that was co-created by a mixed gendered team of complementary strengths, experiences, and competencies – as one would expect from a functional team. The papers in this issue of the journal again embrace the diversity of planning cultures in Europe and beyond. They address themes ranging from transport to open space planning. Interdisciplinarity, qualitative and quantitative analytical approaches, design and strategy, and research and education are all covered in varying depth and breadth. (Post-)modern planning is diverse, and requires flexibility and openness to change; in our complex world the future is not predetermined but shaped and evolving. This fourth issue is a good example of this diversity; with a geographical focus spanning from Mexico, Portugal to Russia and Italy, it explores planning approaches (resilience-based planning) as well as knowledge management issues and social behaviours.